Pola Pemanfaatan Media Sosial Instagram pada Mahasiswa Universitas Muhammadiyah Sumatera Utara - Lubis, Chandra Halim; Sikumbang, Ahmad Tamrin (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2024)
This study examines the pattern of social media utilization of Instagram among students of Universitas Muhammadiyah Sumatera Utara, which is increasingly becoming an integral part of their daily lives. This research was conducted by examining the increasing use of social media among the younger generation and its impact on social interaction and academic performance. The purpose of this study was to understand how university students utilize Instagram in social and academic contexts, and to explore the motivations behind their use of the platform. The focus of the research includes various aspects, such as frequency of use, types of content shared, and its influence on students’ social and academic lives. The research method used was a qualitative approach involving four informants selected based on certain criteria, namely students from various study programs and levels. Data was collected through in-depth interviews and analysis of content shared on Instagram. The results showed that Instagram is used as an effective communication tool, a means of sharing information, and a medium for building personal identity. Informants revealed that they feel more connected to their friends and academic community through this platform. The novelty found in this study is that students not only use Instagram for fun, but also as a source of motivation and inspiration in learning, with educational content that they follow. The findings provide a new contribution to understanding the dynamics of social media use among university students in the digital era.